Elmer and the Wind - McKee, David (Chicago : Milet, 2010)
Elmer the patchwork elephant experiences wind, storms, fog, snow, and other kinds of weather. Presented in English and Polish.
1.4
K-3
Text in English
Translated from the English.
Cover title.
On board pages.
Keywords: Elmer (Fictitious character : McKee) -- Juvenile fiction; Weather -- Juvenile fiction; Elmer (Fictitious character : McKee) -- Fiction; Weather -- Fiction; Bilingual; Elmer (Fictitious character : McKee) -- Fiction; Weather -- Fiction; English-